Multiple blockholders and earnings management - Jiang, Fuxiu; Ma, Yunbiao; Wang, Xue (Journal of Corporate Finance, 2020)
This paper examines the impact of multiple blockholders on earnings management when the main conflict of interest is between controlling shareholder and other shareholders. Using a sample of Chinese listed firms from 2000 to 2017 and controlling for potential sample selection and endogeneity, we find that firms with multiple blockholders tend to have higher earnings management than firms with a single controlling shareholder. The positive impact of multiple blockholders on earnings management is more pronounced when those blockholders are the same type – state or private. Earnings management is also enhanced with more large shareholders and higher relative ownership of other large shareholders to the controlling shareholder. The results are consistent with the cost-sharing hypothesis, where the other large shareholders shoulder the costs of earnings management with the controlling shareholder proportionally, but not the private benefits of control. Further tests show that the positive relation between multiple large shareholders and earnings management is less pronounced in firms with stronger internal or external governance. Overall, our paper demonstrates a potential dark side of multiple blockholders from the angle of financial reporting quality.